Enhancing efficiency of nitrogen removal from wastewater in constructed wetlands - Shved, Oleksa; Petrina, Romana; Chervetsova, Veronika; Novikov, Volodymyr (Eastern-European Journal of Enterprise Technologies, 2015)
This study contributes to the enhancement of nitrogen removal, as well as to the understanding of internal nitrogen transformation processes in horizontal subsurface flow constructed wetlands. Constructed wetlands of this type are able to efficiently remove polluting organic materials, total suspended solids and pathogens from sewage, but nitrogen removal is usually of relatively low efficiency. However, constructed wetlands are a competitive sustainable alternative for conventional wastewater treatment technologies. The primary objective was to evaluate the influence of plants and anaerobic ammonium oxidation (anammox) bacteria on the treatment performance of the wetlands in order to improve the management of these systems. Laboratory-scale horizontal subsurface flow wetland mesocosms were set up in the specialized reactors. The experimental system consisted of three planted fixed bed reactors with a volume of 19.5 L and a surface area of 0.040 m2 each. Two of the reactors were planted with Juncus effusus and one was kept unplanted. All systems were fed with synthetic wastewater containing ammonium (NH4+)as a main contaminant. Hydraulic loading rate was fixed at 45 mm d-1. In accordance with the varying operational conditions, the total experimental period was divided into three phases. During the last phase of the experimental period one of the planted reactors was inoculated with an enrichment culture of anammox bacteria. In summary, experimental results have shown that prompting of anammox process by inoculation of externally enriched biomass could be of tremendous importance for increasing the effectiveness of nitrogen removal in horizontal subsurface flow constructed wetlands.